2021
DOI: 10.1111/bcp.15017
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for under‐ and overdosing of direct oral anticoagulants and physicians' implementation of clinical pharmacists' recommendations

Abstract: To analyse the appropriateness of direct oral anticoagulant (DOAC) dosing and determinants for under-and overdosing as well as acceptance and implementation rates of pharmacists' interventions. Methods: Cross-sectional study in a tertiary hospital in hospitalized patients with atrial fibrillation on DOACs in 2019 (n = 1688). Primary outcome was the proportion of patients with inappropriate DOAC prescribing with identification of determinants for under-and overdosing. Secondary outcomes included acceptance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
2
15
1
Order By: Relevance
“…propriate NOAC therapy of which the acceptance rate ranged from 58.3% to 92.6% (with an overall acceptance rate of 71.3%). In their analyses on pharmacist recommendations for NOAC prescriptions, Perlman et al 13 and Moudallel et al 16 found a similar acceptance of more than 70% and 79.2%, respectively. Most of our recommendations pertained to inappropriate NOAC dosing (68.6%).…”
Section: Observational Study During the Postimplementation Periodmentioning
confidence: 92%
See 3 more Smart Citations
“…propriate NOAC therapy of which the acceptance rate ranged from 58.3% to 92.6% (with an overall acceptance rate of 71.3%). In their analyses on pharmacist recommendations for NOAC prescriptions, Perlman et al 13 and Moudallel et al 16 found a similar acceptance of more than 70% and 79.2%, respectively. Most of our recommendations pertained to inappropriate NOAC dosing (68.6%).…”
Section: Observational Study During the Postimplementation Periodmentioning
confidence: 92%
“…This was also observed in other studies evaluating pharmacist-led interventions for NOAC treatments. [13][14][15][16] The clinical rules on NOAC dosing considered a multitude of decision modifiers, including indication, renal function and age, but also contraindications and clinically relevant drug interactions. These many factors add to the difficulty of selecting the correct dose.…”
Section: Observational Study During the Postimplementation Periodmentioning
confidence: 99%
See 2 more Smart Citations
“…Underdosing of NOACs has been observed in several countries [74,[76][77][78][79][80]. Dosing of rivaroxaban (adjusted according to kidney function) may be simpler than that of other NOACs, which is slightly more limited by various factors (creatinine, weight, age, treatment with P-glycoprotein inhibitors).…”
Section: Underdosingmentioning
confidence: 99%